KEARIFAN LOKAL DAN KECERDASAN EKOLOGIS DALAM PEMBELAJARAN BAHASA DAN SASTRA INDONESIA SEBAGAI UPAYA MENUJU INDONESIA EMAS 2045 - Doni Uji Windiatmoko (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to describe the learning of Indonesian language and literature based on local wisdom and ecological intelligence. This research is a literature study with a qualitative descriptive approach. The results of the study stated that local wisdom and ecological intelligence can be integrated in learning Indonesian language and literature so that the teaching and learning process in the classroom can run optimally and students get a pleasant and effective learning experience. Competencies, learning outcomes, and indicators of Indonesian language and literature subjects are getting richer but intensive based on the conservation of local cultural excellence and understanding of the environment towards Indonesian Gold 2045. Keywords: learning Indonesian language and literature, local wisdom, ecological intelligence, and learning experiences and Indonesian Education 2045